Modelling and Optimization of Rice (Oryza sativa L.) Paddy Pre-Treatments for Optimum Chemical Property using Response Surface Methodology - Oludolapo A, Osunrinade; R, Akinoso (Journal of Food Technology Research, 2020)
Rice (Oryza sativa L. variety OS-6) paddy pre-treatments condition was optimized with respect to proximate, amylose and free fatty acids (FFA) composition. Soaking duration (1, 3 and 5 days), initial soaking temperature (30, 65 and 100 0C), parboiling temperature (80, 100 and 120 0C) and drying temperature (30, 50 and 70 0C) were used as independent factors in D-optimal response surface design methodology. AOAC methods were used for determination of proximate and free fatty acid composition. Amylose content was determined using standard method. Moisture, ash, fat, protein, crude fibre, carbohydrate, amylose contents and FFA of the rice were 4.22- 10.24%, 0.24-0.71%, 0.62-1.73%, 7.41-9.57%, 0.60-1.71%, 78.31-84.65%, 17.41-22.34% 25 and 0.70-3.80%, respectively. The R2 for the model fitted ranged from 0.457 to 0.922. The range of R2 and p-value obtained for moisture, carbohydrate, energy, FFA and amylose affirms the degree of fitness of models obtained. The optimum rice paddy pre-treatment condition obtained was 1 day: 4.8 minutes, initial soaking temperature of 35 oC, Parboiling temperature of 98.03 oC and drying temperature of 70 oC